The potential of cannabinoids in the treatment of lung cancer - Drozd, Małgorzata; Marzęda, Paweł; Czarnota, Jakub; Dobrzyński, Michał; Skubel, Tomasz; Dudek, Iga; Rybak, Natalia (Journal of Education, Health and Sport, 2022)
Introduction: Lung cancer is the number-one cause of death due to neoplasms worldwide. The 5-year overall survival rate is only 22%. In advanced stages, the therapeutic options are limited to chemotherapy, radiotherapy, molecularly targeted therapy and immunotherapy. Phytocannabinoids, the components of Cannabis sativa, their synthetic derivatives and endogenous cannabinoids have demonstrated anticancer activity in various common cancers - breast, prostate, colorectal and lung cancers, among others. The aim of this review was to assess the potential value of cannabinoids in the treatment of lung cancer. State of knowledge: The majority of preclinical studies demonstrates that cannabinoids inhibit lung cancer cell viability both in vitro and in vivo. The main mechanism of anticancer activity is the induction of apoptosis, triggered by activation of CB1, CB2 and TRPV1 receptors or independently via other pathways. Cannabinoids influence the components of the tumour microenvironment - cancer associated fibroblasts, macrophages and lymphokine-activated-killer cells. Cannabinoids alter leukocyte infiltration into anti-cancer proportions, inhibit expression of EGFR and PAI-1 and increase the expression of TIMP-1. As a result they induce cytotoxicity, decrease proliferation, migration and invasive potential of lung cancer cells, suppress angiogenesis and metastasis forming. Patients with advanced lung cancer may also benefit from analgesic, antiemetic and appetite improving properties of cannabinoids. Summary: Cannabinoids can be a supplementary agent in systemic anticancer therapeutic regimen in the future. The exact mechanisms of action, specific doses in anticancer treatment, routes of administration and interactions with other anticancer drugs has yet to be determined. Thus the clinical studies on cannabinoids in lung cancer should be performed in the future.